Graphite-doped negative electrode material and preparation method and application thereof
By adopting the doping method of core-shell structure in the graphite negative electrode material, the core of element-doped graphite secondary particles is formed and vapor-phase deposition carbon coating is carried out, which solves the problem of poor performance of existing graphite negative electrode materials under fast charging and high magnification, and achieves more efficient fast charging performance and kinetic performance.
Patent Information
- Application Number
- CN202510007728.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
AI Technical Summary
The existing graphite negative electrode materials perform poorly at fast charging and high magnification, and the doping process is insufficient uniformity, which limits the improvement of the fast charging performance of the material.
The doped graphite negative electrode material using a core-shell structure forms the core of element-doped graphite secondary particles through solid or liquid phase doping, and forms a dense and uniform carbon coating layer on its surface by vapor deposition.
It significantly improves the fast charging and kinetic performance of graphite negative electrode materials, reduces side reactions with the electrolyte, and improves the overall performance of the material.
Smart Images

Figure CN119725497A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrode materials for rechargeable secondary batteries, and in particular to a doped graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] Graphite has become the most widely used negative electrode material for lithium-ion batteries due to its good electrical conductivity, cycle stability, abundant resources, and low price. However, the layered structure of graphite determines the + It can only be embedded from the end face of the material and gradually diffuse into the interior of the particle, resulting in Li + The long diffusion path and the small interlayer spacing (0.335nm) also limit the Li + The movement of graphite leads to poor fast charging performance of the material, large charge and discharge polarization at high rates, and the risk of lithium precipitation. The current methods to improve the fast charging performance of graphite are mainly: 1) reducing the size and shortening the migration path of lithium ions; 2) making it into a porous structure to increase the lithium ion migration channel and increase the electrolyte wettability; 3) coating treatment, coating a layer of soft carbon or hard carbon on the surface of graphite can increase the interlayer spacing, thereby improving fast charging, but simple carbon coating also causes the deterioration of high temperature performance, because the coated carbon layer is usually an amorphous structure and is more likely to have side reactions with the electrolyte; 4) element doping, the role of element doping can be summarized as follows: first, it changes the microstructure and electronic arrangement of graphite materials, increases the electron and ion transmission rate, and improves the fast charging performance; second, it forms some defects to increase the active sites on the surface of the material, which is conducive to the shuttle of lithium ions and thus improves the kinetic performance; third, it expands the interlayer spacing of graphite to improve the rate performance, and at the same time has a certain improvement on the capacity. Common doping elements include N, P, B, S, O, F elements, etc.
[0003] Patent CN116022781B mixes the carbon source precursor and the doped boron source, heats them in sections, and finally graphitizes them to obtain a boron-doped graphite negative electrode material, which not only ensures the stability of the battery, but also improves the capacity, compaction, and fast charging capabilities. Patent CN117342552A mixes the raw coke and metallic potassium, introduces heteroatom gas doping after programmed temperature increase, then graphitizes to store energy, and finally performs gas-phase carbon coating to obtain heteroatom-doped porous graphite. The raw coke is expanded by the gasification of potassium, and a graphite negative electrode with a large interlayer spacing is obtained after graphitization, which improves the fast charging performance of the material, and improves the electronic conductivity and rate performance by doping heteroatoms at the defects of the raw coke.
[0004] The above technical solutions lack reasonable structural design for the doping of graphite negative electrode materials, and the doping process is not optimized. The doping uniformity is poor and the improvement of the fast charging performance of the material is limited. Summary of the invention
[0005] The purpose of the present invention is to provide a doped graphite negative electrode material that can improve the fast charging performance of a rechargeable secondary battery; another purpose of the present invention is to provide a method for preparing a graphite negative electrode material with more reasonable and uniform doping; another purpose of the present invention is to provide an application of a doped graphite negative electrode material.
[0006] The invention discloses a doped graphite negative electrode material, which is a core-shell structure, comprising an inner core and a shell outside the inner core; the inner core is element-doped doped graphite secondary particles; the doping method of the doped graphite secondary particles is solid-phase doping or liquid-phase doping; the shell is a carbon coating layer with doped elements formed by vapor deposition; the total mass of the doped elements in the inner core and the shell accounts for 0.5-10% of the mass of the doped graphite negative electrode material.
[0007] The doping element is a mixture of one or more of N, B, P, S, F, and O.
[0008] The outer layer of doped carbon coating is a vapor deposition coating, which is more dense and uniform, and can well isolate the direct contact between the inner core of the doped graphite secondary particles and the electrolyte, thereby reducing the side reactions with the electrolyte.
[0009] The doping source of the doped carbon coating layer is gas phase, and the doping is more uniform. Solid phase doping can only rely on the penetration and reaction between particles. Compared with solid phase deposition doping, gas phase deposition doping is relatively more uniform.
[0010] Furthermore, the total mass of the doping elements accounts for 2-5% of the mass of the doped graphite negative electrode material.
[0011] The present invention also provides a method for preparing a doped graphite negative electrode material, comprising the following steps:
[0012] S1: mixing a carbon-based material, a dopant, and a bonding carbon source to obtain a mixed material A;
[0013] S2: granulating and sintering the mixed material A, and graphitizing the granulated and sintered material at high temperature to obtain a doped graphite core B;
[0014] S3: crushing the doped graphite core B and sieving;
[0015] S4: introducing carbon source gas, doping source gas and carrier gas, and vapor-depositing a carbon coating layer of doping elements on the surface of the sieved doped graphite core B to obtain the doped graphite negative electrode material as described above.
[0016] Element doping is completed during the process of graphitization and outer carbon coating, without the need for additional steps, with low cost and suitable for large-scale production.
[0017] Furthermore, in step S1, the carbon-based material includes any one of needle coke, petroleum coke, and asphalt coke; the dopant includes a combination of at least two of urea, melamine, boron oxide, boric acid, boron nitride, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphorus pentoxide, sodium sulfate, ammonium persulfate, thiourea, polytetrafluoroethylene, polyvinylidene fluoride, silicon tetrafluoride, and hydrogen peroxide; and the bonding carbon source includes any one of asphalt, resin, and coal tar, or a combination of at least two of them.
[0018] By doping different elements at the same time and utilizing the synergistic effect between the elements, the doping reaction is easier to carry out and the doping effect is better.
[0019] Furthermore, in step S1, the mass ratio of the carbon-based material, the dopant, and the bonding carbon source is (10-25):(0.2-1.5):1.
[0020] The mixing of the carbon-based material, dopant and binding carbon source is solid phase mixing or liquid phase mixing. The solid phase mixing is carried out in a VC mixer, kneader or ball mill to obtain a mixed material A. The liquid phase mixing is carried out by dispersing the materials in an organic solvent and spray drying to obtain a mixed material A.
[0021] Furthermore, in step S2, the granulation and sintering process is: in a protective gas atmosphere, firstly keep the temperature at 200-350°C for 1-3 hours, and then keep the temperature at 800-1000°C for 2-5 hours.
[0022] The primary graphite particles are bonded into secondary particles to improve compaction and low temperature performance. The granulation process is first kept warm at 200-350℃ to soften the bonding carbon source and form a bonding effect, and then carbonized at 800-1000℃ to crack the carbon source into carbon.
[0023] Granulation is carried out in a granulation kettle, which is a horizontal granulation kettle or a vertical granulation kettle. High temperature graphitization is carried out in an Acheson furnace.
[0024] Furthermore, in step S2, the high temperature graphitization treatment conditions are: temperature 2800-3000° C., time 12-24 h.
[0025] Furthermore, in step S4, the carbon source gas includes any one of acetylene, methane, propylene, acetone, and natural gas, or a combination of at least two of them; the doping source gas includes any one of ammonia, diborane, tetraborane, boron fluoride, and phosphine, or a combination of at least two of them; and the carrier gas includes any one of nitrogen, argon, and helium.
[0026] Furthermore, in step S4, the flow ratio of the carbon source gas, the doping source gas, and the carrier gas is 1:(0.2-2.5):(2-5); the temperature of the vapor deposition is 800-1000° C., and the processing time is 2-6 h.
[0027] The present invention also discloses an application of a doped graphite negative electrode material. The doped graphite negative electrode obtained by the preparation method described above is applied to the manufacture of a rechargeable secondary battery.
[0028] Rechargeable secondary batteries include lithium-ion batteries and sodium-ion batteries.
[0029] The doped graphite negative electrode material, conductive agent, binder, etc. are mixed, coated on the current collector, and processed to obtain the negative electrode plate of the rechargeable secondary battery.
[0030] The present invention provides a doped graphite negative electrode material, which adopts a double doping method to perform element doping treatment on the core of the graphite secondary particles and the carbon coating layer; element doping is used to improve the microstructure of the graphite and form active site defects, which is conducive to the diffusion of charge carriers and improves the kinetic properties of the material; at the same time, the distance between graphite layers is enlarged; the carbon coating layer isolates the core of the graphite secondary particles from direct contact with the electrolyte, thereby comprehensively improving the fast charging performance of the doped graphite negative electrode from all directions and angles. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 1 is a schematic diagram of the structure of the doped graphite negative electrode material provided in Example 1 of the present invention; wherein 1 is a carbon coating layer shell doped with nitrogen; 2 is a graphite secondary particle core doped with nitrogen and boron elements;
[0032] Figure 2 is a SEM image of the doped graphite negative electrode material prepared in Example 1 of the present invention;
[0033] Figure 3 It is a charging rate performance diagram of the negative electrode materials prepared in Example 1 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0035] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased through regular channels.
[0036] Example 1
[0037] The preparation method of doped graphite negative electrode material is as follows:
[0038] S1: 2 kg of needle coke, 150 g of asphalt, 50 g of melamine and 100 g of boron oxide were added into a VC mixer and mixed at 1000 r / min for 30 min to obtain a mixed material A.
[0039] S2: Add the mixed material A obtained in step S1 into a horizontal granulation kettle, heat it to 300°C at 5°C / min under a N2 blanket atmosphere, keep it warm for 2 hours, then heat it to 800°C at 2°C / min, keep it warm for 2 hours and then naturally cool it to room temperature; transfer the granulated and sintered material to an Acheson graphitization furnace, treat it at 2800°C for 12 hours, cool it to room temperature after graphitization, and obtain a doped graphite core B.
[0040] S3: The doped graphite core B obtained in step S2 is crushed and passed through a 200-mesh sieve.
[0041] S4: Place the sieved doped graphite core B in a CVD rotary furnace, first pass argon gas at 1 L / min to exhaust the air in the furnace, then raise the temperature to 800°C, adjust the argon flow rate to 3 L / min, and pass 1 L / min ammonia and 1 L / min acetylene gas. Treat for 4 hours to coat the doped graphite core B with a nitrogen-doped carbon layer to obtain a doped graphite negative electrode material.
[0042] like Figure 1 As shown, the prepared doped graphite negative electrode material has a graphite secondary particle core doped with nitrogen and boron elements and a carbon coating layer shell doped with nitrogen elements.
[0043] The doped graphite negative electrode material obtained in Example 1 was subjected to scanning electron microscopy (SEM) to examine its microstructure. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the doped graphite negative electrode material presents a granulated secondary structure.
[0044] Example 2
[0045] The preparation method of doped graphite negative electrode material is as follows:
[0046] S1: 2 kg of petroleum coke, 200 g of asphalt, 100 g of boric oxide and 100 g of diammonium phosphate were added into a VC mixer and mixed at 1000 r / min for 30 min to obtain a mixed material A.
[0047] S2: Add the mixed material A obtained in step S1 into a horizontal granulation kettle, heat it to 280°C at 5°C / min under N2 atmosphere, keep it warm for 2h, then heat it to 800°C at 2°C / min, keep it warm for 2h and then naturally cool it to room temperature; transfer the granulated and sintered material to an Acheson graphitization furnace, treat it at 3000°C for 12h, cool it to room temperature after graphitization, and obtain a doped graphite core B.
[0048] S3: The doped graphite core B obtained in step S2 is crushed and passed through a 200-mesh sieve.
[0049] S4: Place the sieved doped graphite core B in a CVD rotary furnace, first pass argon gas at 1 L / min to exhaust the air in the furnace, then raise the temperature to 850°C, adjust the argon flow rate to 3 L / min, and pass 1 L / min ammonia gas, 1 L / min phosphine gas and 1 L / min acetylene gas, and treat for 4 hours to coat the doped graphite core B with a nitrogen and phosphorus co-doped carbon layer to obtain a doped graphite negative electrode material.
[0050] Comparative Example 1
[0051] The preparation process is the same as that of Example 1, except that in step S1, no nitrogen source melamine and no boron source boron oxide are added when the materials are mixed.
[0052] Comparative Example 2
[0053] The preparation process is the same as that of Example 1, except that in step S4, when the carbon source and argon are introduced, the nitrogen source gas ammonia is not introduced.
[0054] Comparative Example 3
[0055] The preparation process is the same as that of Example 1, except that in step S1, no nitrogen source melamine and boron source boron oxide are added when the materials are mixed; and in step S4, no nitrogen source gas ammonia is introduced when the carbon source and argon are introduced.
[0056] Performance Test:
[0057] The negative electrode materials prepared in Examples 1-2 and Comparative Examples 1-3 were assembled into a model 2032 button battery for evaluation. The specific scheme was as follows: the negative electrode material, conductive agent SP, conductive agent VGCF, and binder LA136D were mixed in a ratio of 75:5:10:10, with water as the solvent, mixed into a slurry, and then the slurry was coated on a copper foil. The counter electrode was a lithium sheet, the diaphragm was a Celgard2400 microporous polypropylene film, the charge and discharge cut-off voltage was 0.005-1.5V, the discharge rate was 0.1C constant current discharge to 0.005V, and then discharged to 0.005V at 0.02C, and the charge rate was 0.1C charge to 1.5V. The test structure is shown in Table 1.
[0058] Table 1 shows the results of the power-off test of Examples 1-2 and Comparative Examples 1-3.
[0059] Material First lithium insertion capacity (mAh / g) First lithium removal capacity (mAh / g) First efficiency (%) Example 1 374.9 352.4 94 Example 2 372.3 350.7 94.2 Comparative Example 1 371.7 347.5 93.5 Comparative Example 2 373.8 345 92.3 Comparative Example 3 372.5 342.7 92
[0060] As shown in Table 1, compared with Comparative Examples 1-3, the doped graphite negative electrode material prepared in Example 1-2 has higher reversible capacity and first efficiency, proving that the double element doping significantly improves the lithium ion and electron transport of the material, while reducing polarization, increasing lithium storage sites and improving capacity, and the overall performance of the negative electrode material is greatly improved.
[0061] At the same time, the button batteries prepared in Example 1 and Comparative Examples 1-3 were subjected to rate performance tests, and the test method was as follows: first, charge to 1.5V with a constant current and constant voltage of 0.1C, and discharge to 0.005V with a constant current of 0.1C for three weeks; then charge to 1.5V with a constant current of 0.5C, and discharge to 0.005V with a constant current of 0.5C, and repeat for three weeks; then charge to 1.5V with a constant current of 1C, and discharge to 0.005V with a constant current of 1C, and repeat for three weeks; then charge to 1.5V with a constant current of 2C, and discharge to 0.005V with a constant current of 2C, and repeat for three weeks; finally, charge to 1.5V with a constant current of 3C, and discharge to 0.005V with a constant current of 3C, and calculate the retention rate of capacity at each charging rate relative to 0.1C to judge the fast charging performance of different materials. The results are as follows Figure 3 shown.
[0062] like Figure 3 As shown, compared with Comparative Examples 1-3, the element doping in Example 1 before and after graphitization can greatly improve the fast charging performance of the graphite material, and the charging capacity at 2C and 3C is significantly improved, which is better than the effect of unilateral doping before or after graphitization (Comparative Examples 1 and 2).
[0063] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A doped graphite negative electrode material, characterized in that: It is a core-shell structure, including an inner core and a shell outside the inner core; the inner core is element-doped doped graphite secondary particles; the doping method of the doped graphite secondary particles is solid phase doping or liquid phase doping; the shell includes a carbon coating layer with doped elements formed by vapor deposition; the total mass of the doped elements in the inner core and the shell accounts for 0.5-10% of the mass of the doped graphite negative electrode material.
2. The doped graphite negative electrode material according to claim 1, characterized in that: The total mass of the doped elements in the core and the shell accounts for 2-5% of the mass of the doped graphite negative electrode material.
3. A method for preparing a doped graphite negative electrode material, characterized in that: The following steps are involved: S1: mixing a carbon-based material, a dopant, and a bonding carbon source to obtain a mixed material A; S2: granulating and sintering the mixed material A, and graphitizing the granulated and sintered material at high temperature to obtain a doped graphite core B; S3: crushing the doped graphite core B and sieving; S4: introducing a carbon source gas, a doping source gas, and a carrier gas, and vapor-depositing a carbon coating layer of the doping element on the surface of the sieved doped graphite core B to prepare the doped graphite negative electrode material as described in any one of claims 1-2.
4. The method for preparing a doped graphite negative electrode material according to claim 3, characterized in that: In step S1, the carbon-based material includes any one of needle coke, petroleum coke, and asphalt coke; the dopant includes a combination of at least two of urea, melamine, boron oxide, boric acid, boron nitride, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphorus pentoxide, sodium sulfate, ammonium persulfate, thiourea, polytetrafluoroethylene, polyvinylidene fluoride, silicon tetrafluoride, and hydrogen peroxide; the bonding carbon source includes any one of asphalt, resin, and coal tar, or a combination of at least two of them.
5. The method for preparing a doped graphite negative electrode material according to claim 4, characterized in that: In the step S1, the mass ratio of the carbon-based material, the dopant, and the bonding carbon source is 10-15:0.5-1.5:
1.
6. The method for preparing a doped graphite negative electrode material according to claim 3, characterized in that: In step S2, the granulation and sintering process is: in a protective gas atmosphere, first keep the temperature at 200-350° C. for 1-3 hours, and then keep the temperature at 800-1000° C. for 2-5 hours.
7. The method for preparing a doped graphite negative electrode material according to claim 6, characterized in that: In the step S2, the high temperature graphitization treatment conditions are: temperature 2800-3000° C., time 12-24 hours.
8. The method for preparing a doped graphite negative electrode material according to claim 3, characterized in that: In step S4, the carbon source gas includes any one of acetylene, methane, propylene, acetone, and natural gas, or a combination of at least two of them; the doping source gas includes any one of ammonia, diborane, tetraborane, boron fluoride, and phosphine, or a combination of at least two of them; and the carrier gas includes any one of nitrogen, argon, and helium.
9. The method for preparing a doped graphite negative electrode material according to claim 8, characterized in that: In the step S4, the flow ratio of the carbon source gas, the doping source gas, and the carrier gas is 1:0.5-2.5:2-5; the temperature of the vapor deposition is 800-1000° C., and the processing time is 2-6 h.
10. An application of a doped graphite negative electrode material, characterized in that: The doped graphite negative electrode material as described in any one of claims 4 to 9 is used in the manufacture of a rechargeable secondary battery.
Citation Information
Patent Citations
Quick-charging graphite composite material, preparation method thereof and battery
CN117342552A
Composite cathode material, preparation method thereof, lithium ion secondary battery negative plate and lithium ion secondary battery
CN105098185A
Graphite negative electrode material for power lithium ion battery and preparation method therefor
CN105609779A
Nitrogen-doped carbon-coated hybrid graphite composite material, preparation method thereof and application in lithium ion battery
CN109449428A
Graphite material with porous carbon layer and preparation method and application thereof
CN114068885A
Cited By
Porous graphite negative electrode material and preparation method and application thereof
CN119976825A
A porous graphite negative electrode material and its preparation method and application
CN119976825B
Graphite composite material, preparation method thereof and lithium ion battery
CN121905847A
Graphite composite material, preparation method thereof and lithium ion battery
CN121905847B